Diffusion pattern of low dose rate brachytherapy for prostate cancer in Japan - Nakamura, Katsumasa (Cancer Sci, 2013)
Permanent implant brachytherapy for prostate cancer using iodine‐125 seeds was adopted in Japan in 2003. Here, we report on the diffusion pattern of this treatment in Japan since 2003. We examined the annual numbers of prostate cancer patients per hospital in Japan, who were treated with iodine‐125 seed implant brachytherapy with or without external beam radiation therapy between 2003 and 2011. The hospitals were excluded from the count if brachytherapy was begun in a hospital within the given year, and thus was only available for part of the year. In 2004, 269 patients were treated by brachytherapy at only two hospitals. However, the numbers increased rapidly. A total of 1412 patients were treated at 23 hospitals in 2005, 2783 patients were treated at 83 hospitals in 2008, and 3793 patients were treated at 109 hospitals in 2011. The mean/median numbers of patients treated per hospital were 61.4/42 in 2005, 33.5/25 in 2008, and 35.0/24 in 2011. The number of hospitals where 24 or fewer patients were treated in a year increased. On the other hand, the number of hospitals with a volume of >48 patients per year was stable. Because a relationship between provider volume and outcomes following oncological procedures was shown, a careful evaluation of the effectiveness of permanent implant brachytherapy for prostate cancer is needed.